An evaluation of factors affecting the progression to clean audit outcomes in South African Municipalities - Motubatse, Kgobalale Nebbel (My University, 2016)
This research examines the effectiveness of the factors that have been introduced to bring about progress to clean audit outcomes in South African municipalities. This research has become increasingly important as the democratic dispensation in South Africa has witnessed a gradual weakening of public financial accountability. As a consequence of this ongoing decline, the National Government initiated the campaign “operation clean audit” as a means to achieve a new level of improved audit outcomes. The Auditor General of South Africa (AGSA) identified three key factors that would drive improved audit outcomes, namely leadership, financial management and governance. Given that “operation clean audit” had seemingly become an elusive dream by 2014, the researcher decided to examine the relative effectiveness of the causative variables identified by the AGSA as key to achieving improved audit outcomes. This research therefore was intended to make a contribution to the body of academic knowledge by pursuing the following objectives: to examine the effect of leadership on the achievement of clean audit outcomes in the South African public service; to analyse the effectiveness of financial management in the South African public service; to evaluate the effect of governance on the achievement of clean audit outcomes in the South African public service, and to propose a framework for understanding the factors that affect clean audit outcomes in the South African public service. To achieve the research objectives, the research applied a positivist paradigm and a quantitative approach. Data were collected from the AGSA’s consolidated municipal reports from the nine provinces of the Republic. Hence, the study was limited to the use of municipal audit reports, consolidated into single reports for all the municipalities in each of the provinces over a period of years. Thus, the study examines a total of nine consolidated reports for each of the five years between 2009/2010 – 2013/2014. Using the panel data approach, this produced a set of nine cross sectional units and 5 periods which thus produced 45 time series observations. Subsequently, a panel data multiple regression analysis was conducted to analyse the data. After correcting the model for heteroskedaskicity, the results from the regression analysis revealed important relationships in only two dimensions. On the one hand, the three independent variables – leadership, financial management and governance – jointly vi have a significant relationship with clean audit outcomes, with a P value P<0.000, which is substantially below the 5% alpha level anticipated for this research. The independent variables were each examined for their individual effects on clean audit results. Results show that only governance has a significant and direct effect on the achievement of a clean audit. Given that governance has a substantially stronger impact on the achievement of clean audits (far more than do the other variables), further analysis was conducted to determine the variables that influence the efficiency of governance. The results reveal that the effectiveness of the audit committee has an overriding influence on the ability of an entity to achieve clean audits. The findings thus appear to confirm the Auditor General’s broad claim that leadership, financial management and governance are the key drivers to improved audit outcomes: but further analysis reveals that this happens only when the three variables are analysed as a single unit, to examine whether they significanly enhance clean audit outcomes. As single variables, only governance proved to affect clean audit outcomes significantly. The findings from the analysis thus corroborates the literature, thus achieving the first three research objectives. Arising from this analysis, the researcher was able to propose a framework for understanding the factors that affect an entity’s progression to clean audit. This constituted the achievement of research objective 4, and makes a contribution to the current body of knowledge on the topic. Thus, this research contributes to knowledge in that it develops a framework for understanding the factors that affect the achievement of a clean audit, and proposes two key approaches to further research and improve public sector auditing: a model to research the variables that affect audit committee effectiveness; and a practical approach that includes additional variables (drawn from the framework) during the public sector audit. Key words Accountability, accounting, audit committee, audit quality, clean audit, financial management, governance, leadership, public administration, public policy, public sector, supreme audit institution.
Thesis (Ph. D. (Public Administration)) -- University of Limpopo, 2016.
Keywords: Acountability; Accounting; Financial management; Auditing; Auditing -- South Africa; Local finance -- Auditing; Finance, Public -- South Africa -- Auditing; Government accountability; Financial institutions -- Management; Municipal governmnent -- South Africa